Package gfp-div-gcd: A GF(p) division algorithm based on gcd

Information

namegfp-div-gcd
version1.66
descriptionA GF(p) division algorithm based on gcd
authorJoe Leslie-Hurd <joe@gilith.com>
licenseMIT
checksum0427fe9142faac0335419f9823398ce951d3ca95
requiresbase
gfp-def
gfp-div-def
gfp-div-thm
gfp-thm
gfp-witness
natural-divides
natural-prime
showData.Bool
Data.Pair
Number.GF(p)
Number.Natural

Files

Defined Constant

Theorems

x y. ¬(y = 0) x / y = divGcd (toNatural y) oddprime x 0

u v x1 x2.
    gcd u v = 1 fromNatural u * x2 = fromNatural v * x1
    fromNatural u * divGcd u v x1 x2 = x1
    fromNatural v * divGcd u v x1 x2 = x2

u v x1 x2.
    divGcd u v x1 x2 =
    if u = 1 then x1
    else if v = 1 then x2
    else if even u then divGcd (u div 2) v (x1 / 2) x2
    else if even v then divGcd u (v div 2) x1 (x2 / 2)
    else if v u then divGcd (u - v) v (x1 - x2) x2
    else divGcd u (v - u) x1 (x2 - x1)

p.
    (v. p 1 v) (u. ¬(u = 1) p u 1)
    (u v. gcd (2 * u) v = 1 ¬(v = 1) p u v p (2 * u) v)
    (u v. gcd u (2 * v) = 1 ¬(u = 1) odd u p u v p u (2 * v))
    (u v. gcd u v = 1 even u ¬(v = 1) odd v p u v p (v + u) v)
    (u v. gcd u v = 1 ¬(u = 1) odd u even v p u v p u (u + v))
    u v. gcd u v = 1 p u v

p.
    (v x1 x2. p 1 v x1 x2 x1) (u x1 x2. p u 1 x1 x2 x2)
    (u v x1 x2 g.
       gcd (2 * u) v = 1 p u v x1 x2 g p (2 * u) v (2 * x1) x2 g)
    (u v x1 x2 g.
       gcd u (2 * v) = 1 p u v x1 x2 g p u (2 * v) x1 (2 * x2) g)
    (u v x1 x2 g.
       gcd u v = 1 p u v x1 x2 g p (v + u) v (x2 + x1) x2 g)
    (u v x1 x2 g.
       gcd u v = 1 p u v x1 x2 g p u (u + v) x1 (x1 + x2) g)
    u v x1 x2. gcd u v = 1 p u v x1 x2 (divGcd u v x1 x2)

External Type Operators

External Constants

Assumptions

prime oddprime

¬

¬

bit0 0 = 0

t. t t

p. p

fromNatural oddprime = 0

t. t ¬t

(¬) = λp. p

() = λp. p ((select) p)

t. (x. t) t

t. (λx. t x) = t

() = λp. p = λx.

t. ¬¬t t

t. ( t) t

t. (t ) t

t. t

t. t t

t. t t

t. t

t. t t

t. t

t. t t

t. t

t. t t

x. fromNatural (toNatural x) = x

n. 0 + n = n

m. m + 0 = m

a. gcd 0 a = a

a. gcd a 0 = a

t. ( t) ¬t

t. (t ) ¬t

t. t ¬t

x. x + 0 = x

n. even (2 * n)

n. bit1 n = suc (bit0 n)

n. ¬even n odd n

n. ¬odd n even n

m. 1 * m = m

m n. m m + n

¬(2 = 0)

() = λp q. p q p

t. (t ) (t )

x. x * 0 = 0

x. 0 * x = 0

x. ~x + x = 0

x. 1 * x = x

m. m 0 m = 0

t1 t2. (if then t1 else t2) = t2

t1 t2. (if then t1 else t2) = t1

p x. p x p ((select) p)

n. 0 < n ¬(n = 0)

n. bit0 (suc n) = suc (suc (bit0 n))

t1 t2. t1 t2 t2 t1

x y. x * y = y * x

x y. x + y = y + x

m n. m + n = n + m

a b. gcd a b = gcd b a

m n. m n n m

m n. m + n - m = n

x. fromNatural x = 0 divides oddprime x

x y. x - y = x + ~y

m n. ¬(m n) n < m

p. (b. p b) p p

() = λp q. (λf. f p q) = λf. f

p. ¬(x. p x) x. ¬p x

p. ¬(x. p x) x. ¬p x

() = λp. q. (x. p x q) q

m n. m + suc n = suc (m + n)

m n. suc m + n = suc (m + n)

m n. n < m + n 0 < m

a b. gcd a (a + b) = gcd a b

a b. gcd (b + a) b = gcd a b

t1 t2. ¬(t1 t2) ¬t1 ¬t2

t1 t2. ¬(t1 t2) ¬t1 ¬t2

m n. even (m + n) even m even n

x1 y1. fromNatural (x1 * y1) = fromNatural x1 * fromNatural y1

x1 y1. fromNatural (x1 + y1) = fromNatural x1 + fromNatural y1

n. even n m. n = 2 * m

p. (x. p x) a b. p (a, b)

m n. m n d. n = m + d

() = λp q. r. (p r) (q r) r

m n. m n n m m = n

f. fn. a b. fn (a, b) = f a b

m n. m < n d. n = m + suc d

p q. (x. p q x) p x. q x

p q. p (x. q x) x. p q x

p q. p (x. q x) x. p q x

p q. p (x. q x) x. p q x

m n. ¬(m = 0) m * n div m = n

p q. (x. p x) q x. p x q

p q. (x. p x) q x. p x q

p q r. p q r p q r

x y z. x * y * z = x * (y * z)

x y z. x + y + z = x + (y + z)

x y z. x + y = x + z y = z

x. ¬(x = 0) inv x * x = 1

m n p. m + n < m + p n < p

m n p. n + m < p + m n < p

m n p. m + n m + p n p

x y. ¬(x = 0) x * (y / x) = y

m n. m * n = 0 m = 0 n = 0

p. p 0 (n. p n p (suc n)) n. p n

x y. ¬(x = 0) y / x = y * inv x

p n. prime p ¬divides p n gcd p n = 1

x y z. x * (y + z) = x * y + x * z

x y z. (y + z) * x = y * x + z * x

p. (n. (m. m < n p m) p n) n. p n

p g h. f. x. f x = if p x then f (g x) else h x

p q. (x. p x) (x. q x) x. p x q x

x y. x * y = x x = 0 y = 1

x y z. x * y = x * z x = 0 y = z

m n p. m * p < n * p m < n ¬(p = 0)

x y z. ¬(x = 0) x * y = x * z y = z

a b c. gcd a (b * c) = 1 gcd a b = 1 gcd a c = 1

a b c. gcd (b * c) a = 1 gcd b a = 1 gcd c a = 1